Single‐pill combination of cilnidipine, an L‐/N‐type calcium channel blocker, and valsartan effectively reduces home pulse pressure in patients with uncontrolled hypertension and sympathetic hyperactivity: The HOPE‐Combi survey. Issue 3 (20th April 2020) - Kario, Kazuomi; Matsuda, Saori; Nagahama, Shinobu; Kurose, Yoshiki; Sugii, Hitoshi; Teshima, Tsukasa; Suzuki, Noriyuki
Abstract: The home blood pressure (BP) control by a single‐pill combination of cilnidipine (an L‐/N‐type calcium channel blocker; CCB) and valsartan (HOPE‐Combi) survey is a multicenter, post‐marketing, prospective observational study of a single‐pill combination of cilnidipine 10 mg and valsartan 80 mg (SPC of Cil/Val) in patients with uncontrolled hypertension. We examined the effects of the SPC of Cil/Val on morning home systolic BP (MHSBP) and morning home pulse pressure (MHPP) of 1036 patients with hypertension over 12 months. MHSBP decreased by 14.0 mm Hg ( P < .01), and MHPP decreased by 6.6 mm Hg ( P < .01). Moreover, morning home pulse rate (MHPR) decreased by 2.1 bpm ( P < .01). A more progressive and greater decrease in MHSBP (−17.2 vs −10.3 mm Hg, P < .01) and MHPP (−7.6 vs −4.9 mm Hg, P < .01) was observed in patients with higher MHPR (≥70 bpm) than in those with lower MHPR (<70 bpm) over the treatment period. In particular, in patients with a wide MHPP (≥70 mm Hg), the difference in the MHPP reduction was greater in patients with higher MHPR than in those with lower MHPR (−17.9 vs −13.6 mm Hg, P < .01). These results suggested that the SPC of Cil/Val, which possesses the unique sympatholytic characteristics of an L‐/N‐type CCB, was particularly effective in patients with uncontrolled hypertension and sympathetic hyperactivity.